Discriminatory experiences among gay, bisexual, and other men who have sex with men, and transgender and non-binary individuals: a cross sectional analysisResearch in context - Lucilene Freitas; Thiago S. Torres; Brenda Hoagland; Mayara S.T. Silva; Valdilea G. Veloso; Beatriz Grinsztejn; João L. Bastos; Paula M. Luz (Elsevier, 2024)
Summary: Background: Several systems of oppression combine in complex ways to impact the lives of minority populations. Following an intersectionality framework, we assessed the frequency and perceived reasons for discrimination among gay, bisexual, and other cisgender men who have sex with men (MSM) and transgender and non-binary individuals (TGNB), stratified by race. Methods: Online survey among MSM and TGNB ≥18 years living in Brazil, between November/2021 and January/2022. We used the 18-item Explicit Discrimination Scale to assess day-to-day experiences of differential treatment, and perceived discrimination. For each item, participants indicated their perceived reasons for differential treatment using 14 pre-defined options. Negative binomial regression models assessed if race was a significant predictor of discrimination. Subsequent models, stratified by race, examined associations of perceived reasons and number of reasons with perceived discrimination. Findings: Of 8464 MSM and TGNB, 4961 (58.6%) were White, 2173 (25.7%) Pardo (Brazil's official term for admixed populations), and 1024 (12.1%) Black. Black participants' scores for perceived discrimination (mean, standard deviation) were higher (10.2, 8.8) [Pardo (6.5, 6.8), White (5.2, 5.7)], and race was both the main reason for and the strongest predictor of perceived discrimination. The number of reasons participants used to interpret their discriminatory experiences was also a predictor of discrimination score among White, Pardo, and Black participants. Interpretation: LGBTQIA+phobia was highly prevalent among all participants. Additionally, our results indicated that Black MSM and TGNB participants were more frequently discriminated against than other racial groups, with racial discrimination uniquely contributing these experiences. Funding: Fundação Oswaldo Cruz, Conselho Nacional de Desenvolvimento Científico e Tecnológico, Fundação Carlos Chagas Filho de Amparo à Pesquisa do Estado do Rio de Janeiro.